Digital technologies as a factor in increasing the efficiency of state and municipal government - G.P. Sorokina; L.V. Shirokova; I.A. Astafeva (Интеллект. Инновации. Инвестиции, 2019)
The Article is devoted to the topical issue of the introduction and use of digital technologies and their impact on improving the efficiency of public administration in the context of obtaining the expected result of social orientation, focused on the interests of the end user – the population and business. Digitalization of the public sector at its various levels is aimed at improving the business environment, the well-being of citizens, raising their awareness and digital literacy, ensuring maximum accessibility and achieving a high level of quality of public services. The article deals with the negative factors that prevent the implementation of an intensive process of digitalization, and, consequently, improve the efficiency of public administration. The purpose of this article is to review the process of digitalization of the sphere of state and municipal management, the analysis of statistical, reflecting the scope and scale of its digital development, to identify aspects that negatively affect the quality of services provided by the authorities. The methods of comparative and factor analysis, synthesis and generalization became the main methods of the problem research. The results: the analysis of the introduction of digital technologies in the sphere of state and municipal administration, reflected the positive social effects achieved through the transition to the digital format of management, systematized reasons hindering this process, proposed measures to minimize the impact of the considered adverse factors, of which the most significant are the improvement of administrative regulations and standards for the provision of state and municipal services, legal and methodological support for the interaction of information systems at the departmental and regional levels, increasing digital literacy of the population, the elimination of social inequality in the digital space. Direction of using the achieved results: the materials of the article will be of interest to researchers and practitioners, graduate students and students.